ANALISIS PERFORMANSI VOICE OVER INTERNET PROTOCOL (VOIP) BERBASIS SESSION INITIATION PROTOCOL (SIP) PADA JARINGAN WIRELESS LAN IEEE 802.11 UNIVERSITAS LAMPUNG - Nama, Gigih Forda; Septama, Hery Dian (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2014)
Nowadays Voice over Internet Protocol (VoIP) technology are widely used by humans being to communicate. VoIP allows the transmission of voice data packets from one place to another, over an Internet Protocol (IP), VoIP technology was adopted in Lampung University to provide a cheap and effective communication around internal campus, there are total 250 subscribers VoIP extension, spread out and used by Faculty member and Administration unit by IPPhone or Soft phone. This paper evaluates the quality of the Unila VoIP infrastructure services by measuring substantial parameters such is delay, jitter, packet loss, Mean Opinion Score (MOS) in 802.11 wireless LAN media using software tools VQ Manager. The results shown that the quality of VoIP through the wireless network goes well, shown from the value of the average MOS 4.4. , Delay <250 ms, jitter <30 ms, packet loss <5% (refer to ITU standards).